2014
DOI: 10.1007/s00402-014-2099-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diclofenac on matrix metalloproteinase levels in the rotator cuff

Abstract: Diclofenac has an impact on the levels of MMP-2, MMP-3 and MMP-13, which are needed for normal healing process, and it can also lead to disruption of tendon healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The rats were killed at post-operative weeks 1, 3, and 6. The humerus and supraspinatus muscle dissected from the rest of the body to form a tendon-humeral unity after exposing the acromial arc without giving any harm to the healing portion of the tendon 16 .…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were killed at post-operative weeks 1, 3, and 6. The humerus and supraspinatus muscle dissected from the rest of the body to form a tendon-humeral unity after exposing the acromial arc without giving any harm to the healing portion of the tendon 16 .…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…For examining vascular proliferation, a 30.000 micron square meter was chosen at the tendon bone healing region where maximum vascularity exists. Newly formed vessels were counted and 0-5 vessels classified as 1, 6-20 classified as 2 and above 21 as 3 16,17 .…”
Section: Histologymentioning
confidence: 99%
“…Traditional nonselective NSAIDs inhibit both COX1 and COX2, while selective NSAIDs only target COX2 (Table ). For rotator cuff repair, a number of NSAIDs, including diclofenac, meloxicam, ibuprofen, indomethacin, and celecoxib, showed largely detrimental effects on mechanical properties and tendon healing after acute injury . These effects may be somewhat time‐dependent; while most studies showed impaired healing with immediate delivery postinjury, delivery at later stages of healing did not seem to affect functional properties .…”
Section: Biomolecule‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
“…For rotator cuff repair, a number of NSAIDs, including diclofenac, meloxicam, ibuprofen, indomethacin, and celecoxib, showed largely detrimental effects on mechanical properties and tendon healing after acute injury. [85][86][87][88] These effects may be somewhat time-dependent; while most studies showed impaired healing with immediate delivery postinjury, delivery at later stages of healing did not seem to affect functional properties. 87 Indeed, delayed repair coupled with licofelone injections (a dual COX and lipoxygenase inhibitor) improved mechanical properties and fibrocartilage deposition.…”
Section: Immunomodulatory Factorsmentioning
confidence: 99%
“…Of particular relevance in orthopaedic surgery, the use of the non-steroidal anti-inflammatory drug (NSAID) diclofenac was shown to significantly influence levels of MMP-2, MMP-3 and MMP-13 after rotator cuff repair in a rat model, eventually resulting in decreased biomechanical strength of the repair [ 29 ]. Cohen et al demonstrated inferior healing and lower rotator cuff repair loads to failure in rats receiving celecoxib and indomethacin compared to contols [ 30 ].…”
Section: Matrix Metalloproteinase (Mmp) Inhibitorsmentioning
confidence: 99%